APLIKASI METODE GEOLISTRIK UNTUK MENYELIDIKI INTRUSI AIR LAUT DI KAWASAN PANTAI KOTA SEMARANG (KALIGAWE) - Dhana Hastuti; Fitra Ramdhani; Fajar Waskito; Galang Virgiawan; Ganap Yuliana Febrika; Agus Setyawan (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2015)
Kaligawe is a village in East Semarang, Central Java, Indonesia. Rising population lead to increased ground water extraction and land use. Excessive groundwater abstraction resulting height difference surface ground water to the surface of the sea water, causing sea water intrusion. To determine the value of the depth of seawater intrusion areas of research conducted using resistivity method. Data is collected as much as 3 lines. The field data in the form of current, potential difference, and apparent resistivity processed. Then made modeling 2D with Res2Dinvx32 software to produce the actual resistivity and depth of each layer of the earth's subsurface. The results showed seawater intrusion occurs in the northwest, east and south of the study area is shown with a small resistivity of 2.07-13.2 Ωm at a depth of 0-35 m below the earth's surface.